PERAN DIGITAL MARKETING INNOVATION UNTUK MENINGKATKAN MARKETING PERFORMANCE MELALUI BUSINESS PROCESS AGILITY PADA UKM DI JAWA TENGAH - Wesly Tumbur ML Tobing; Risma Nurhapsari; Lukman Santoso; Paulina Kinanti Eka Praningtyas (CV. Denasya Smart Publisher, 2025)
This study began with differences in views from several researchers about the relationship between digital marketing innovation and marketing performance. With the results of this study, the research we conducted tried to conduct research by implementing business process agility so that there is a significant relationship between digital marketing innovation and marketing performance. This study was conducted by collecting data through direct distribution of questionnaires or through the use of Google Forms to respondents who are SME owners in Central Java Province. The sampling technique was carried out purposively with the criteria that SMEs have been operating for at least 5 years, where the number of samples obtained was 211 SME owners who met these criteria. The data was analyzed using Amos 22, where the results of the study showed a positive and significant relationship between digital marketing innovation and marketing performance. In addition, there is a positive and significant relationship between digital marketing innovation and business process agility and a positive and significant relationship between business process agility and marketing performance.